STUDENT TEACHERS’ CHALLENGES IN DEVELOPING TEACHING MATERIALS DURING TEACHING PRACTICUM IN VOCATIONAL SCHOOL - Dian Rahayuningsih (Journal of English and Education, 2016)
Teaching practicum is an essential time for pre service teacher in practicing their teaching skills. It shows the student teachers ability in applying the knowledge that they have learned from the college to the real school and social environments. This study aimed to investigate the student teachers challenges in developing teaching materials during teaching practicum in vocational school and how they overcome the problems. Qualitative approach was employed in this research to understand, describe and explain beliefs, behaviors and meaning in context-specific settings (Wu Volker, 2009) and case study used to capture the complexity of a single case (Johansson, 2003). The participants of this study were two English student teachers enrolled in teaching practicum in the eighth semester of the academic year 2015/2016. The data were collected through in-depth interview related to student teachers teaching experience in developing teaching materials in vocational school. The findings of the study revealed that the challenges faced by student teachers in developing material include (1) the lack of student teachers knowledge on students’ field, (2) the lack of supervisi